<u>f(x) = x + 3</u>
f(2) = 2 + 3
f(2) = 5
f(4) = 4 + 5
f(4) = 9
f(6) = 6 + 5
f(6) = 11
{(2, 5), (4, 9), (6, 11)}
Answer:
(6x+12y)
Step-by-step explanation:
answer is helpful or not
(2/3),=(1/2), 3,4
.
............................
The unit rate will be in revolutions per second. That means divide number of revolutions by number of seconds.
first convert from mixed fraction.
6 2/5 = 32/5 revolutions
2 2/3 = 8/3 seconds
32/5 ÷ 8/3
flip multiply
32/5 × 3/8 = 12/5 revolutions per second
12/5 = 2 2/5 revolutions per second